2012
DOI: 10.1007/s00066-012-0258-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of transrectal ultrasonography for assessment of cervical cancer

Abstract: The feasibility of TRUS for the assessment of local target extension could be demonstrated. Comparison of the target width and thickness showed a high correlation between TRUS and MRI, indicating the potential of TRUS for target definition in image-guided adaptive brachytherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Another approach by transrectal ultrasound (TRUS) was performed by Schmid et al (24) reporting TRUSand MRI-guided correlations for conformal intracavitary AE interstitial BT in cervical cancer. The study identified a mean maximum target width of 4.2 AE 0.83 and 4.2 AE 0.79 cm for MRI and TRUS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach by transrectal ultrasound (TRUS) was performed by Schmid et al (24) reporting TRUSand MRI-guided correlations for conformal intracavitary AE interstitial BT in cervical cancer. The study identified a mean maximum target width of 4.2 AE 0.83 and 4.2 AE 0.79 cm for MRI and TRUS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Typical 74 dose gradients at the border of a target are as high as 5-20% per mm. 75 The pronounced dose gradients result in a highly heterogeneous 3D 76 dose distribution, and the median target dose is typically higher than and hypofractionation leads to a significant enhancement of the 94 biological effect leading to an ablative effect in the high dose regions. 95 Due to the physical characteristics and the biological effects it is possible 96 to routinely deliver more than e.g.…”
Section: Image Guided Therapymentioning
confidence: 99%
“…These results showed that TVS was superior to MRI in both women with and without cone biopsy prior to surgery (12). Schmid et al discussed using transrectal ultrasound (TRUS) to assess cervix cancer during radiation therapy (13). The cervix was examined in 17 patients using TRUS and the findings compared with those of MRI.…”
Section: Tod Et Al Formulated the Manchester System In 1938mentioning
confidence: 99%